SOCIOHISTORICAL PRECONDITIONS OF THE PRIVATE LAND PROPERTY - Pryadka, T. M.; Chumachenko, O. M. (Землеустрій, кадастр і моніторинг земель, 2012)
Historicsl aspects of development of a private land property within the territory of Ukraine are investigated. The course of the main land reforms, the directions of their realization and results of carrying out are considered in a historical cut.